1991
DOI: 10.1002/cne.903110207
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic varicosities make synaptic contacts with pleural sensory neurons of Aplysia

Abstract: Serotonin is a modulatory neurotransmitter that produces many of the cellular changes associated with sensitization of reflexes in Aplysia. These changes have been carefully documented in sensory neurons located in the abdominal ganglion that mediate the gill-siphon withdrawal reflex and in sensory neurons located in the pleural ganglion that mediate the tail-siphon withdrawal reflex. Although serotonin appears to be necessary for sensitization, there is no direct evidence that serotoninergic neurons make syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…5-HT, acting through phospholipase C-coupled receptors (Li et al, 1995), stimulates the translocation and transient activation of PKC in tail SNs (Sacktor and Schwartz, 1990;Sossin and Schwartz, 1992). Studies of the serotonergic innervation in the ring ganglia, coupled with direct amperometric measurements of 5-HT release, suggest that 5-HT release is distributed across the majority of the, if not the entire, population of SN synapses (Zhang et al, 1991;Marinesco and Carew, 2002). Thus, PKC will be activated in all tail SNs exposed to 5-HT as a consequence of tail shock.…”
Section: Pkm In Synaptic Plasticity and Memorymentioning
confidence: 99%
“…5-HT, acting through phospholipase C-coupled receptors (Li et al, 1995), stimulates the translocation and transient activation of PKC in tail SNs (Sacktor and Schwartz, 1990;Sossin and Schwartz, 1992). Studies of the serotonergic innervation in the ring ganglia, coupled with direct amperometric measurements of 5-HT release, suggest that 5-HT release is distributed across the majority of the, if not the entire, population of SN synapses (Zhang et al, 1991;Marinesco and Carew, 2002). Thus, PKC will be activated in all tail SNs exposed to 5-HT as a consequence of tail shock.…”
Section: Pkm In Synaptic Plasticity and Memorymentioning
confidence: 99%
“…Moreover, sensitizing stimulation leads to release of serotonin (Levenson et al 1999;Marinesco and Carew 2002). Previous studies using immunocytochemistry and electron microscopy demonstrated contacts between serotonergic processes and the cell body and processes of sensory neurons (Kistler Jr. et al 1985;Zhang et al 1991), but little is known regarding the relationship of serotonergic inputs to sensorimotor contacts. Using confocal microscopy as described above, we examined the relationship of serotonergic axons to pairs of sensory and motor neurons.…”
Section: Proximity Of Serotonergic Input To Sensorimotor Contactsmentioning
confidence: 99%
“…Morphological evidence indicates that serotonergic neurons provide input to sensory neurons Kistler Jr. et al 1985;Zhang et al 1991). The structural proximity of serotonergic processes would enable elevated levels of intracellular second messengers and activated protein kinases to diffuse to nearby synapses and phosphorylate target proteins.…”
mentioning
confidence: 99%
“…The finding of 5-HT-immunoreactive fibers in contact with siphon sensory neurons (Kistler et al 1985) supports the hypothesis that serotonergic neurons contribute to behavioral sensitization. Numerous serotonergic varicosities have also been observed surrounding somata and axon hillocks of tail sensory neurons (Zhang et al 1991). Electron microscopy confirmed that these contacts were directly on the membrane of sensory neurons and were presumably synaptic in nature.…”
Section: The Siphon-elicited and Tail-elicited Reflex Withdrawal Circmentioning
confidence: 85%
“…These results suggest that 5-HT is released from varicosities directly onto somata of sensory neurons, eliciting the cellular changes correlated with sensitization. The proximity of serotonergic input to the soma may be crucial for triggering the cellular mechanisms underlying the long-term form of sensitization (Kistler et al 1985;Nazif et al 1991;Zhang et al 1991;Bacskai et al 1993;Clark and Kandel 1993;Emptage and Carew 1993;O'Leary et al 1995).…”
Section: The Siphon-elicited and Tail-elicited Reflex Withdrawal Circmentioning
confidence: 99%